Schisandrins as novel efflux pumps inhibitors and non-antibiotic compounds against multi- and extensively-drug resistant clinical strains of Salmonella typhi: An in-vitro study - Iqra Shafique; Nosheen Fatima Rana; Naseer Ahmad; Tahreem Tanweer; Sabah Javaid; Fawzyah Obeedallah Albaldi; Serag Eldin I. Elbehairi; Ali A. Shati; Huda M. Sheikh; Farid Menaa (PLoS ONE, 2026)
Purpose Typhoid is a significant global health challenge due to its high pathogenicity and antimicrobial resistance. Salmonella typhi ( S.typhi ) can switch its lifestyles between biofilm and planktonic phase which allows it to evade host defenses and develop resistance to antibiotics. Salmonella sp. harbors multiple genes encoding efflux-pumps systems whose up-regulation contributes to multi-drug resistance (MDR) and extensive drug-resistance (XDR). To overcome the battle against resistant S. typhi strains, novel non-antibiotics inhibitors are required for inhibitory application. This study assesses the inhibitory effect of lignans against drug resistance of S. typhi . Methods Clinical resistant and sensitive strains of S. typhi were obtained and characterized. The inhibitory effect of lignans, specifically Schisandrin A and B, purified from the plant Schisandra chinensis , are found to be effective non-antibiotic inhibitors were evaluated through standard microbiological techniques like growth curve and time-kill assays. Impact on bacterial morphology was analyzed using scanning electron microscopy (SEM). Our study explores two approaches, such as efflux pumps (EPs) inhibition and antibiofilm assays. Results Using colony-forming unit (CFU) assays, growth curve analysis, and SEM imaging, we observed significant bacteriostatic effects, with Schisandrin B causing notable membrane disruption. Schisandrin B also showed remarkable biofilm inhibition (90.33%) and strong efflux pumps inhibition. Conclusion This study offers a strong basis for future research on addressing antibiotic resistance in clinically relevant pathogens.